Save the bengal tiger! - Lopez, Billy; Berger, Cassandra; Little Airplane Productions (New York : Simon Spotlight/Nick Jr., 2008)
Raji the mouse and the Wonder Pets help the tiger by removing a thorn in her paw and teaching her that all animals are special.
"Based on the TV series Wonder Pets as seen on Nick Jr."--T.p. verso.
3.5
K-3
Keywords: Mice -- Juvenile fiction; Pets -- Juvenile fiction; Tigers -- Juvenile fiction; Mice -- Fiction; Pets -- Fiction; Tigers -- Fiction; Mice -- Fiction; Pets -- Fiction; Radio and television novels; Tigers -- Fiction; Radio and television novels